The Joy of Lottery Play: Evidence from a Field Experiment - Martijn J. Burger; Martijn Hendriks; Emma Pleeging; Jan C. van Ours (Tinbergen Institute, 2018)
We conducted a field experiment to increase our understanding of lottery participation. Using representative data for the Netherlands, we find that lottery participation increased the happiness of participants before the draw. Winning a small prize had no effect on happiness. Our results indicate that people may not only care about the outcomes of the lottery, but also enjoy the game. Accordingly, we conclude that lottery play has a utility value in itself and part of the lottery ticket is consumed before the draw.
Keywords: C93; I31; 330; lottery play; happiness; field experiment